Surgical Treatment of Lymphedema: A Systematic Review and Meta-Analysis of Controlled Trials. Results of a Consensus Conference. Issue 4 (19th March 2021) - Chang, David W.; Dayan, Joseph; Greene, Arin K.; MacDonald, John K.; Masia, Jaume; Mehrara, Babak; Neligan, Peter C.; Nguyen, Dung
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The goal of this consensus conference, sponsored by the American Association of Plastic Surgeons, was to perform a systematic review and meta-analysis of controlled trials to examine both the benefits and risks of surgical treatment and surgical prevention of upper and lower extremity lymphedema. Methods: The panel met in Boston for a 3-day, face-to-face meeting in July of 2017. After an exhaustive review of the existing literature, the authors created consensus recommendations using the Grading of Recommendations, Assessment, Development and Evaluation criteria. Important directions for future research were also identified. Results: There is evidence to support that lymphovenous anastomosis can be effective in reducing severity of lymphedema (grade 1C). There is evidence to support that vascular lymph node transplantation can be effective in reducing severity of lymphedema (grade 1B). Currently, there is no consensus on which procedure (lymphovenous bypass versus vascular lymph node transplantation) is more effective (grade 2C). A few studies show that prophylactic lymphovenous bypass in patients undergoing extremity lymphadenectomy may reduce the incidence of lymphedema (grade 1B). More studies with longer follow-up are required to confirm this benefit. Debulking procedures such as liposuction are effective in addressing a nonfluid component such as fat involving lymphedema (grade 1C). There is a role for liposuction combined with physiologic procedures although the timing of each procedure is currently unresolved (grade 1C). Conclusions: Many studies seem to support some efficacy of lymphovenous bypass and vascular lymph node transplantation. Many studies show the important role of lymphedema therapy and other procedures such as liposuction and debulking. The management of lymphedema is a challenging field with many promising advances. However, many questions remain unanswered.